Antiretroviral therapy adherence and functional health literacy of adults living with HIV/AIDS - Raquel Dias da Silva Santos; Guilherme Guarino de Moura Sá; Clícia Meyriele de Oliveira Bezerra Gonçalves; Katarinne Lima Moraes; Maria Wanderleya de Lavor Coriolano-Marinus; Estela Maria Leite Meirelles Monteiro; Tatiane Gomes Guedes (Rev Rene)
Objective: to analyze the association between antiretroviral therapy adherence and functional health literacy among adults living with HIV/AIDS. Methods: a coss-sectional study with 69 patients from a specialized HIV/AIDS care service. The Questionnaire for Assessing Antiretroviral therapy adherence the Test of Functional Health Literacy short version were used. Descriptive and inferential analyses were employed. In the analysis, the Chi-square test was used to verify the association between functional literacy levels and classification of antiretroviral therapy adherence, and Fisher’s exact test was used to determine associations between therapy adherence classification and independent variables. Results: insufficient antiretroviral therapy adherence (76.8%) and adequate functional health literacy (63.8%) were identified. There was no significant association between antiretroviral therapy adherence and sociodemographic variables or functional literacy levels. However, an association was identified between antiretroviral therapy adherence and self-rated health (p=0.012). Conclusion: there was no association between antiretroviral therapy adherence and functional health literacy levels among adults living with HIV/AIDS, but adherence was associated with self-rated health. Contributions to practice: the findings may guide nurses in adapting educational approaches and identifying specific patients who may require additional support or personalized strategies.